Resolving glass transition in Te-based phase-change materials by modulated differential scanning calorimetry. (26th September 2017) - Chen, Yimin; Mu, Sen; Wang, Guoxiang; Shen, Xiang; Wang, Junqiang; Dai, Shixun; Xu, Tiefeng; Nie, Qiuhua; Wang, Rongping
Abstract: Glass transitions of Te-based phase-change materials (PCMs) were studied by modulated differential scanning calorimetry. It was found that both Ge2 Sb2 Te5 and GeTe are marginal glass formers with Δ T (= T x − T g ) less than 2.1 °C when the heating rate is below 3 °C min −1 . The fragilities of Ge2 Sb2 Te5 and GeTe can be estimated as 46.0 and 39.7, respectively, around the glass transition temperature, implying that a fragile-to-strong transition would be presented in such Te-based PCMs. The above results provide direct experimental evidence to support the investigation of crystallization kinetics in supercooled liquid PCMs.